Formulasi dan Uji Aktivitas Antibakteri Sediaan Gel Ekstrak Daun Sirsak (Annona Muricata L.) terhadap Bakteri Pseudomonas Aeruginosa - Cristin Natali Rouli; Muhammad Yunus; Asyrun Alkhairi Lubis (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Soursop leaves (Annona muricata L.) are known to contain secondary metabolites such as alkaloids, flavonoids, tannins, saponins, and polyphenols, which have antibacterial potential. This study aimed to formulate soursop leaf extract into a gel dosage form and to evaluate its antibacterial activity against Pseudomonas aeruginosa. This research was conducted as an experimental laboratory study. Soursop leaf extract was obtained using the maceration method with 96% ethanol as the solvent and then formulated into gel preparations with extract concentrations of 5%, 10%, and 15%. Physical evaluation of the gel preparations included organoleptic test, homogeneity, pH, spreadability, and viscosity. Antibacterial activity was evaluated using the well diffusion method on Nutrient Agar medium. The results showed that all gel formulations met the physical requirements for topical preparations. The antibacterial activity test demonstrated that the soursop leaf extract gel inhibited the growth of Pseudomonas aeruginosa, with the 15% concentration producing the largest inhibition zone of 10 mm compared to other concentrations. In conclusion, soursop leaf extract gel has potential to be developed as a topical antibacterial agent against Pseudomonas aeruginosa.